(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
This case control study was conducted in the Department of Obstetrics and Gynecology, Chittagong Medical College Hospital, in the period from April 07 to March 08. A total of 232 multiparous pregnant women were included in this study; among them 51 were cases (with placenta praevia) and 181 were similar matched control. Past mode of delivery were explored in both the groups and analyzed statistically. Out of 232 subjects, prior caesarean delivery had 25.5% (n=13) in cases and 44.2% (n=80) in controls. After statistical analysis, caesarean section was considered as a risk factor for placenta praevia in subsequent pregnancy. The odds ratio = 0.43 (CI 0.22 – 0.86) and chi square test = 5.80 (df =1; p= 0.016). Key words: Placenta praevia; caesarean section. DOI: 10.3329/bjpp.v25i1.5740 Bangladesh J Physiol Pharmacol 2009; 25(1&2) : 13-17